0994 Sleep Disturbance Mediates The Relationship Between Maternal Parenting And The Schizotypal Personality Traits. (27th April 2018) - Dong, F; Shi, S; Liu, J
Abstract: Introduction: Schizotypal personality traits has been identified as a risk factor for schizophrenia, which is a chronic disabling mental disorder that affects 0.5% of the worldwide adolescents. Growing research has linked maternal parenting to schizotypal personality in health population. However, the pathways explaining this association remain unclear. Research shows sleep disturbances was associated with both schizotypal personality and maternal parenting. Therefore, this study aims to investigate the role of sleep disturbances on the relationship between maternal parenting and schizotypal personality among pre-adolescence in China. Methods: This cross-sectional study consists of a sample of 475 children who were in their sixth grade from in Jintan City, China. Positive and negative maternal parenting was assessed using Parent Bonding Inventory, Schizotypal Personality traits was assessed by Schizotypal Personality Questionnaire, and sleep disturbances was assessed using sleep items in Youth Self Report. The study examines the association among maternal parenting, sleep disturbances and schizotypal personality while controlling for age and gender, focusing on mediation effect of sleep disturbance using PROCESS procedure. Results: Among the 475 participants, 248 are boys, mean age is 12.00± .42 years. After controlling for age and gender, positive maternal parenting was associated with total schizotypal personality ( B =.18, se =.028, p <.001) and sleep disturbance ( B =-.045, se =.012, p <.001). After controlling for sleep disturbance, the amount of variance in total schizotypal personality explained by positive maternal parenting was reduced from 18.2% to 16.3%. The Sobel test confirmed this was a statistically significant reduction ( z = 2.67, p =.008). As the residual variance in schizotypal personality explained by positive maternal parenting was still statistically significant, sleep disturbance partially mediated this association. And similarly, sleep disturbance partially mediated the association between negative maternal parenting and schizotypal personality traits. Conclusion: We found that maternal parenting is associated with the schizotypal personality traits, and sleep disturbances is significantly related to both maternal parenting and schizotypal personality traits. Furthermore, sleep disturbances mediates this association. This preliminary analysis will aid our further understanding of the role of sleep disturbances in developing schizotypal personality. Support (If Any): None.